FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KOMPETENSI PETANI RUMPUT LAUT DI KABUPATEN KONAWE PROVINSI SULAWESI TENGGARA - Hartina Batoa; Amri Jahi; Djoko Susanto (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2008)
The seaweed farmers who are competent indicated by their positive behavior on technical and management of sea weed farming. The objectives of the study are: (1) To find the sea weed farmers characteristics in relation to their competence in sea weed farming management; (2) To find evidence how they practice on sea weed farming; (3) To analyse the relationship between the sea weed farmers characteristics and their competence in sea weed farming. The study was desigred as a descriptive correlation, the data were analyzed using qualitative and quantitative methods same important results are: (1) Majority of the farmers are old age, they have enough experiences in sea weed farming, they have frequently interacted with the extension educator; (2) Most of the farmers have enough competent in: a) Selecting the seeds; b) Harvesting; c) Planting; d) Post harvest management; e) Marketing; and f) Preparation of the farming. There were high significant correlation between age, education, experiences, areal of farming, family dependent members, interaction with the extention educator, and the farmers competencies.